2013
DOI: 10.1002/jso.23427
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete excisions of extremity soft tissue sarcomas are unaffected by insurance status or distance from a sarcoma center

Abstract: Inappropriate excision of STS is not influenced by patient distance from a sarcoma center or by a patient's insurance status. In this study, tumor size, depth, and certain histology types predicted the appropriate referral of a STS to a sarcoma center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The upper extremity is a more frequent site for unplanned excision (35.4%) than it is for planned excision (22.5%) (p < 0.05) 19 ; however, other investigators have reported the knee to be the most common site 15 . Most authors have reported unplanned excisions to be more common in patients with superficial tumors 11 .…”
Section: Locationmentioning
confidence: 97%
See 4 more Smart Citations
“…The upper extremity is a more frequent site for unplanned excision (35.4%) than it is for planned excision (22.5%) (p < 0.05) 19 ; however, other investigators have reported the knee to be the most common site 15 . Most authors have reported unplanned excisions to be more common in patients with superficial tumors 11 .…”
Section: Locationmentioning
confidence: 97%
“…Alamanda et al 19 compared 253 patients undergoing planned excision with 147 patients undergoing reexcision after unplanned excision of soft-tissue sarcomas and found that distance from a sarcoma center (p = 0.69) and insurance status (p = 0.43) were not risk factors for unplanned excision.…”
Section: Insurance Status and Distance From A Sarcoma Centermentioning
confidence: 99%
See 3 more Smart Citations